Lichens of the Hel Peninsula - Wiesław Fałtynowicz; Bogumiła Wojtyła-Kuchta (Acta Mycologica, 2014)
The paper contains a list of 131 lichen species collected in Hel Peninsula (western part of Polish Baltic coast). The current lichen flora of this area comparises only 116 species, we have not found 15 taxa which have been recordered earlier.